Diretrizes orientadoras para plano de gestão de bibliotecas de instituições de ensino superior: um estudo de campo na Universidade Federal de Santa Maria (UFSM) - Lunkes, Ivete Maria Klein (2019)
The study aimed to propose guidelines directives for Libraries Management Plan of IES, in the light of the Self-assessment requirements of Gespública and Axes of the Institutional Evaluation Instrument and Evaluation of Undergraduate Courses of SINAES/INEP/MEC, in order to help as a facilitator in evaluation processes from UFSM, the libraries of the Library System of UFSM and the IES, obtaining institutional indicators of quality for the services provided to society, with practice and continuous improvement actions, for the achievement of higher education of excellence. The theoretical foundation included three main topics, guiding the research: The Libraries, the National System of Higher Assessment SINAES and the National Program of Public Administration and Bureaucracy, the Gespública. As for the method, the study is characterized as a descriptive exploratory field research, applied with a qualitative approach and deductive logic, held in UFSM-SiB/UFSM. To achieve the goal, were identified and analyzed the evaluation requirements of the evaluation Instrument of SINAES, that impact the management of libraries; analyzed the requirements of assessment of the self-evaluation Instrument of Gespública, relevant to the management of libraries and management practices have been identified, and the institutional Library System Libraries of UFSM and that meet these requirements. The data were collected through personal interviews and semi-structured, conducted in loco, with two groups of managers from UFSM, directly linked to the management of libraries in addition to documental analysis complemented with the note. At the same time, it was applied a "checklist" to the same respondents, based on the Self-assessment Instrument of Public Management-IAGP-250 points, the Gespública, structured into eight criteria and seventy-two points. Were also carried out the collection and analysis of secondary data through documentary analysis and research in management documents of other libraries IFES to identify practices and actions adopted (strengths), with respect to libraries. There was also research on the Development Plan of the Educational Unit UFSM (PDU), which stood out positively in data collection, by its practices, initiatives and actions. Interviews with managers from UFSM revealed many positive points-strengths, in management practices, but also proved challenging, troubling and even points of peculiar characteristics, with opportunities for improvement. UFSM managers pointed out obstacles and made recommendations with suggestions for changes for a successful implementation of the plan. The "checklists", in the First Self-evaluation of each group of managers, presented results with important strengths, but also opportunities for improvement, with revelations that deserve strategic actions and mutual commitment between SiB managers and the university management. Investigations in other documents IFES and in document PDU (2018-2022), in the unity of UFSM, showed ways to the success of the proposed goal, as results listed in the dissertation. Finally, based on the results of the research, presented the proposed Directives to Management Plan for Libraries of IES, in particular for UFSM, field of research study. It is concluded that these guidelines may act as tools to aid in the improvement of the Process of Management of Libraries and implementation of the Management Plan for Libraries of IES, culminating in the achievement of institutional goals (Teaching Excellence, University of Excellence, with institutional indicators of excellence and Concept 5 in all evaluations of Mec).